Assesment of Frequency of Distal Radius Fracture in Tertiary Care Hospital (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Fracture of the distal radius is one of the most common fractures. It has been estimated to account for one-sixth of all fractures that are seen and treated in the emergency department. No other fracture has a greater potential to devastate hand function. Understanding the epidemiology of distal radius fractures may be of great importance to clinicians for identifying the risk groups and protect them.Objective: The aim of the present study was to asses the frequency of distal radius fracture. Methods: A prospective observational study was conducted from July 2016 to June 2018 among 32 patients attending at Orthopaedics and Traumatology department of the Dhaka Medical College Hospital after obtaining requisite consent from the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to know the epidemiology of distal radius fracture. The study was approved by the institutional ethical committee.Results: 32 patients were enrolled for the study. The mean age of the patients was 37.56±11.82. More than half of the respondents were male (68.75%). Highest number (31.25%) of patients came from worker community. The commonest cause (62.52%) of distal radius fracture was road traffic accidents. Most of the patients (78.12%) had closed fractures. Out of 32 patients only 6 patients had associated major injury which represents 25.01%.Conclusion: Male and elderly populations are considered at high risk for distal radius fracture.J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 11-12